Pengaruh Disiplin dan Motivasi Kerja terhadap Kinerja Guru pada SMAN 1 Canduang Kabupaten Agam - Siska, Adilla Juita (Jurusan PIPS FKIP UMMY Solok, 2017)
This study aims to identify and analyze the effect of discipline and motivation to work on teacher performance. The population in this study were teachers in SMAN 1 Canduang Agam. Samples taken as many as 35 respondents using census techniques. The data analysis methods that I use in conducting this research is using validity and reliability test, descriptive analysis of variables, multiple linear regression analysis, T test and F test. From the analysis that has been done, it is known that the work discipline variable (X1) positive and significant effect on the performance of teachers, it is evidenced by a significant probability value to the work discipline is 0,001 less than 0.05. It was identified that work motivation (X2) has positive and significant effect on the performance of teachers, it is proved by the probability of significant value to the work motivation of 0,003 is much smaller than 0.05.